2021
DOI: 10.2147/rmhp.s323839
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Nurses’ Knowledge, Attitude, and Practice of Pressure Injury Prevention in China: A Cross-Sectional Study

Abstract: Background: Pressure injury (PI) remains a critical health issue worldwide. The global incidence of hospital-acquired PI is 8.4%, and among intensive-care unit (ICU) patients, it is even higher, ranging from 6.60% to 36.80%. It is important to investigate ICU nurses' PI prevention knowledge, attitudes, and practices (KAP). Aim: The aim of this study was to describe the level of Chinese ICU nurses' knowledge, attitudes, and self-reported practices of PI prevention. Materials and Methods: From March 31 to April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…These findings are in line with Sönmez (2022) (19) reported that the majority of participants nurses were less than 30 years and also Mohamed & Weheida (2019) (20) found that the majority of nurses working in ICU had a secondary education and technical institute of nursing. On the other hands, these findings were disagreed with Zhang et al (2021) (21) and Hu et al (2021) (22) they concluded that most of the sample in their studies had aged more than 30 years and bachelor's level of education.…”
Section: Discussionmentioning
confidence: 67%
“…These findings are in line with Sönmez (2022) (19) reported that the majority of participants nurses were less than 30 years and also Mohamed & Weheida (2019) (20) found that the majority of nurses working in ICU had a secondary education and technical institute of nursing. On the other hands, these findings were disagreed with Zhang et al (2021) (21) and Hu et al (2021) (22) they concluded that most of the sample in their studies had aged more than 30 years and bachelor's level of education.…”
Section: Discussionmentioning
confidence: 67%
“…In one of the included studies, the authors assigned values according to the item's degree of difficulty and significance. Items 1,6,15,24,27,33,34,36,40,41, and 42 received a score of 2.0; statements 2, 3, 5, 8, 9, 13, 14, 16, 21, 23, 25, 26, 28, 30, 37, and 30, received a score of 1.5; and items 4, 7, 10, 11, 12, 17, 18, 19, 20, 22, 29, 31, 32, 35, and 39, received a score of 1.0. The scoring scores were developed by three wound specialist nurses after content validation.…”
Section: Resultsmentioning
confidence: 99%
“…The authors rated the level of knowledge as sufficient 80% correct answers, different from the original version. The instrument was validated for content (CVI 0.97) and had an intraclass correlation coefficient of 0.72 27 .…”
Section: IVmentioning
confidence: 99%
“…The knowledge instruments have been evaluated in different cultural contexts. 21,22 The original version of the PUKAT was translated from English into Swedish, 23 but…”
Section: Instrument Developmentmentioning
confidence: 99%